TOM5 regulates the mitochondrial membrane potential of alveolar epithelial cells in organizing pneumonia - Yan Qian; Xiao Li; Xinyu Li; Xijie Zhang; Qi Yuan; Zhengxia Wang; Mingshun Zhang; Mao Huang; Ningfei Ji (Taylor & Francis Group, 2024)
Deficiency of TOM5, a mitochondrial protein, causes organizing pneumonia (OP) in mice. The clinical significance and mechanisms of TOM5 in the pathogenesis of OP remain elusive. We demonstrated that TOM5 was significantly increased in the lung tissues of OP patients, which was positively correlated with the collagen deposition. In a bleomycin-induced murine model of chronic OP, increased TOM5 was in line with lung fibrosis. In vitro, TOM5 regulated the mitochondrial membrane potential in alveolar epithelial cells. TOM5 reduced the proportion of early apoptotic cells and promoted cell proliferation. Our study shed light on the roles of TOM5 in OP.